IMPLEMENTASI CSR DAN BIAYA LINGKUNGAN DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT DI PT TENANG JAYA SEJAHTERA - Ubaidillah, Raka; Septiawati, Rohma; Purwandari, Dian (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study analyzes the implementation of Corporate Social Responsibility (CSR) and environmental costs in supporting sustainability practices at PT Tenang Jaya Sejahtera. The method used is descriptive qualitative through observation and interviews to explore the reality of implementation in the field. The results show that the company's CSR program includes free healthcare services, social assistance, and the utilization of waste into useful products. Environmental cost management is realized through investments in waste processing technology and emission control. The integration of these two aspects strengthens the achievement of the Triple Bottom Line principle and contributes to social, economic, and environmental sustainability. These findings emphasize the importance of continuous innovation and evaluation so that CSR programs remain effective and relevant to community needs and environmental regulatory demands.